Effect of UV-Assisted RTA on the Electrical Properties of (Ba,Sr)TiO3 Films for Low Temperature Embedding of Decoupling Capacitor - Cho, Kwang-Hwan; Kang, Min-Gyu; Kang, Chong-Yun; Yoon, Seok-Jin; Lee, YoungPak; Kim, Jong-Hee; Cho, Bong-Hee (ELECTROCHEMICAL SOC INC, 2009)
Polycrystalline Ba0.4Sr0.6TiO3 (BST) thin films grown at 350 degrees C with UV-assisted rapidly thermal annealing (RTA) showed a high-k value of 183 at 100 kHz. The 100 nm thick BST film with UV-assisted RTA exhibited a high capacitance density of 16.2 fF/mu m(2) and a low dissipation factor of 0.48% at 100 kHz with a low leakage current density of 1 X 10(-8) A/cm(2) at 0.5 MV/cm. The quadratic and linear voltage coefficients of capacitances of the BST film with UV-assisted RTA were -155 ppm/V-2 and 231 ppm/V, respectively. All these make the BST decoupling capacitor very suitable for use in radio-frequency circuits and mixed-signal integrated circuits. (C) 2009 The Electrochemical Society. [DOI: 10.1149/1.3243858]
Keywords: MIM CAPACITORS; THIN-FILMS; PERFORMANCE